Russia: the war of establishment in Africa - (:unkn) unknown (My University, 2023)
Taking up the legacy of the USSR, Russia has begun to establish itself in Africa by penetration of the most unstable of countries through the use of military might. The paramilitary Wagner Group is one of Moscow’s strong arms, earning its keep through pillage of natural resources such as gold.
Keywords: African Research